Interest rates and foreign spillovers - Roberto A. De Santis; Srečko Zimic (European Central Bank (ECB), 2019)
We show that medium-term interest rates in the euro area, Japan, UK and US are affected by domestic and foreign shocks. We find that US rates are the main source of spillovers globally and are less exposed to foreign shocks. Foreign spillovers to European rates were negligible only during the sovereign debt crisis and the introduction of more aggressive monetary policies by the ECB. We identify causal relations among asset prices through structural vector autoregressions (SVAR) and magnitude restrictions. We use preliminary regressions on event days to estimate key parameters employed to constrain the structural parameter space of the SVAR.
Keywords: C3; G2; 330; Money market rates; Spillovers; Event-study; Magnitude restrictions; SVAR